Country characteristics and acute diarrhea in children from developing nations: A multilevel study (2015)
Background: Each year 2.5 billion cases of diarrheal disease are reported in children under five years, and over 1,000 die. Country characteristics could play a role on this situation. We explored associations between country characteristics and diarrheal disease in children under 5 years of age, adjusting by child, mother and household attributes in developing countries. Methods: This study included 348,706 children from 40 nations. We conducted a multilevel analysis of data from the Demographic and Health Surveys and the World Bank. Results: The prevalence of acute diarrhea was 14 %. Country inequalities (OR = 1.335; 95 % CI 1.117-1.663) and country's low income (OR = 1.488; 95 % CI 1.024-2.163) were associated with diarrhea, and these country characteristics changed the associations of well-known determinants of diarrhea. Specifically, living in poor countries strengthens the association of poor household wealth and mother's lack of education with the disease. Other factors associated with diarrhea were female sex of the child (OR = 0.922; 95 % CI 0.900-0.944), age of the child (OR = 0.978; 95 % CI 0.978-0.979), immunization status (OR = 0.821; 95 % CI 0.799-0.843), normal birthweight (OR = 0.879; 95 % CI 0.834-0.926), maternal age (OR = 0.987; 95 % CI 0.985-0.989), lack of maternal education (OR = 1.416; 95 % CI 1.283-1.564), working status of the mother (OR = 1.136; 95 % CI 1.106-1.167), planned pregnancy (OR = 0.774; 95 % CI 0.753-0.795), a nuclear family structure (OR = 0.949; 95 % CI 0.923-0.975), and household wealth (OR = 0.948; 95 % CI 0.921-0.977). Conclusions: Inequalities and lack of resources at the country level in developing countries -but not health expenditure- were associated with acute diarrhea, independently of child, family and household features. The broad environment considerably modifies well-known social determinants of acute diarrhea and public health campaigns designed to target diarrhea should consider macro characteristics of the country. © 2015 Pinzón-Rondón et al.